Targeting macrophagic SHP2 for ameliorating osteoarthritis via TLR signaling - Ziying Sun; Qianqian Liu; Zhongyang Lv; Jiawei Li; Xingquan Xu; Heng Sun; Maochun Wang; Kuoyang Sun; Tianshu Shi; Zizheng Liu; Guihua Tan; Wenqiang Yan; et al. (Acta Pharmaceutica Sinica B, 2022)
Osteoarthritis (OA), in which M1 macrophage polarization in the synovium exacerbates disease progression, is a major cause of cartilage degeneration and functional disabilities. Therapeutic strategies of OA designed to interfere with the polarization of macrophages have rarely been reported. Here, we report that SHP099, as an allosteric inhibitor of src-homology 2-containing protein tyrosine phosphatase 2 (SHP2), attenuated osteoarthritis progression by inhibiting M1 macrophage polarization. We demonstrated that M1 macrophage polarization was accompanied by the overexpression of SHP2 in the synovial tissues of OA patients and OA model mice. Compared to wild-type (WT) mice, myeloid lineage conditional Shp2 knockout (cKO) mice showed decreased M1 macrophage polarization and attenuated severity of synovitis, an elevated expression of cartilage phenotype protein collagen II (COL2), and a decreased expression of cartilage degradation markers collagen X (COL10) and matrix metalloproteinase 3 (MMP3) in OA cartilage. Further mechanistic analysis showed thatSHP099 inhibited lipopolysaccharide (LPS)-induced Toll-like receptor (TLR) signaling mediated by nuclear factor kappa B (NF-κB) and PI3K–AKT signaling. Moreover, intra-articular injection of SHP099 also significantly attenuated OA progression, including joint synovitis and cartilage damage. These results indicated that allosteric inhibition of SHP2 might be a promising therapeutic strategy for the treatment of OA.